Microglia Phenotype Diversity - Olah, M.; Biber, K.; Vinet, J.; W.G.M. Boddeke, H. (CNS & Neurological Disorders - Drug Targets, 2011)
Microglia, the tissue macrophages of the brain, have under healthy conditions a resting phenotype that is characterized by a ramified morphology. With their fine processes microglia are continuously scanning their environment. Upon any homeostatic disturbance microglia rapidly change their phenotype and contribute to processes including inflammation, tissue remodeling, and neurogenesis. In this review, we will address functional phenotypes of microglia in diverse brain regions and phenotypes associated with neuroinflammation, neurogenesis, brain tumor homeostasis, and aging.
Keywords: white matter